2014
DOI: 10.1039/c3ra45661g
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic rivalry of o-aminophenol-carboxylic acids initiates production of hemi-actinomycins in Streptomyces antibioticus

Abstract: Actinomycins consist of two pentapeptide lactone rings attached to 2-amino-4,6-dimethyl-3-oxophenoxazine-1,9-dicarboxylic acid (actinocin). The actinocin moiety is formed through oxidative condensation of two 3-hydroxy-4-methylanthranilic acid (4-MHA) pentapeptide lactones (actinomycin halves) as the last step of actinomycin biosynthesis. We found that feeding of 4-MHA or its putative biogenetic precursor 3-hydroxyanthranilic acid (3-HA) to Streptomyces antibioticus induced formation of different new compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The pathways for the production of the C‐demethyl derivatives and their biochemical characterization are described in the study of Crnovčić et al . For the hemi ‐actinomycins such data are presented in another recent paper …”
Section: Resultsmentioning
confidence: 99%
“…The pathways for the production of the C‐demethyl derivatives and their biochemical characterization are described in the study of Crnovčić et al . For the hemi ‐actinomycins such data are presented in another recent paper …”
Section: Resultsmentioning
confidence: 99%
“…The annotation of this MF was guided by DEREPLICATOR and VarQuest annotations as well as the Mass2Motif that 10 of its members shared. We could annotate this Mass2Motif as the amino acid lactone loop present twice in actinomycins using reference data from literature [45]. The unique combination of four actinomycin-related mass fragments was only present in the 10 MF members, thereby reinforcing the DEREPLICATOR and VarQuest annotations.…”
Section: Case Study 3: Large Chemical Diversity Uncovered By Annotatimentioning
confidence: 76%
“…Accordingly, the proton in position 4 of the proline moiety gave a multiplet at δ =4.31 ppm, which was not seen in the spectrum of PPL 1, and this confirmed that the 4‐position of the proline ring was substituted. These compounds thus have nearly the same structures as natural Acm halves (Scheme ) but cannot react with each other to yield Acms and therefore accumulate in the cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Strains and cultures : S. chrysomallus ATCC 11523, Streptomyces parvulus ATCC 12434, and S. antibioticus ATCC 14888 (IMRU3720) were maintained and grown as described previously . Mycelium used for biotransformation experiments was from 80 h old cultures (actively synthesizing Acms) of S. antibioticus grown in previously described chemically defined media .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation